Research on inter-core crosstalk characteristics of real multi-core fibers with multi-core excitation - Lian XIANG; Hongfeng PAN; Shulin JIN; Weidong SHAO (Tongxin xuebao)
Based on the coupled power theory, the characteristics of optical power and inter-core crosstalk (ICXT) were studied in real multi-core fibers (MCF) with multi-core excitation.According to the simplified coupled power equation of 7-core fiber, the analytical expressions of optical signal power and ICXT in each fiber core were deduced under three multi-core excitation conditions.Simulation results show that, after long-distance transmission, the optical power of each core would converge to a fixed value and reach a dynamic equilibrium state, and its convergence distance decreased exponentially with the increase of bending radius and gradually tended to a fixed value.In addition, in order to study the relationship between multi-core excitation and single-core excitation, the analytical expressions of the power and ICXT in coupled cores were deduced under simultaneous excitation and separate excitation of multi-core.Research shows that the contribution of multi-core excitations to the ICXT of coupled core is irrelevant, and the ICXT of multi-core excitation is equivalent to the sum of the ICXT obtained by the excitation of the cores separately.